Vibration serviceability of a GFRP railway crossing due to pedestrians and train excitation. (15th September 2020) - Russell, J.M.; Wei, X.; Živanović, S.; Kruger, C.
Highlights: Modal analysis was conducted on an FRP bridge in the factory and after installation. Vibration responses were measured due to pedestrian actions and trains passing. Vibrations were compared to guidelines, and recommendations made for extensions. The bridge's properties meant that vibrations do not affect pedestrian comfort. Abstract: Glass Fibre-Reinforced Polymers (GFRPs) are a popular option for pedestrian bridges over railway lines as they cause little disruption for installation or maintenance. However, as they are typically lighter and less stiff than traditional materials there is concern about their dynamic response due to human induced actions and train buffeting. Due to a lack of experimental information, further data is needed if such bridges are to be used on future lines, especially with higher speed limits. This paper presents an experimental investigation of the response of a 14.5 m GFRP truss bridge due to pedestrian loading and train induced vibrations. Vibration modes of interest were identified from impact hammer tests. The vibration responses to a range of human loading scenarios, as well as multiple train passes, were measured. The vibration levels remained low under all conditions, demonstrating that this particular type of GFRP bridge is suitable for railway crossings and that further optimisations may be available to designers while meeting vibration serviceability limits. However, consideration of the loadings suggests GFRP bridges may be more susceptible to higher pedestrian harmonics than traditional structures, and that vibrations from train buffeting are likely to be a design consideration for future bridges over high speed lines.